THE LITERARY HISTORY OF THE FOLK WEREWOLF - Данилюк-Терещук, Т. Я. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article describes the interpretation features of the demonological image of the werewolf in the works of O. Somov and S. Aleksandrov. It is revealed that the archaic semantics of the character becom a universal construct in the ideological and aesthetic organization of the literary text. Folk stories about werewolves unfold in literary stories about unlimited possibilities and extraordinary abilities of the person. In the work of O. Somov, the werewolf appears in the form of a simpleton-fool, a wizard-werewolf, a robber-knight, but S. Aleksandrov’s hero passes the path from the sinner to the blessed. The writers are interested in the psychological state of a person in the wolf’s skin.